Understanding one aspect of the knowledge leakage concept among SMEs: people. (3rd April 2007) - Mohamed, Souad; Coles, Rhoda; Mynors, Diane; Chan, Paul; Grantham, Andrew; Walsh, Kathryn
To guarantee the success of a commercial organisation in the present tremendously competitive world, managers need to enhance best practices and retain in-house knowledge and experience. An organisation's competitive advantage can be lost if knowledge and/or experience is lost or 'leaked'. The research described here explores whether organisations are aware of knowledge leakage routes via people, and the positive and negative consequences that can result. The concept of knowledge leakage is not well understood and the nature of this research is exploratory. This paper discusses the findings of a study carried out in SMEs involved in manufacturing and design. As a result, a taxonomy of knowledge leakage via people with an integrated approach to knowledge 'loss' and 'gain' is proposed.